Diversity and Urgency of Religious Moderation Education According to the Public Perception - Hoktaviandri, Hoktaviandri; Suatri, Suatri; B., Irawati; Ningsih, Sri Susi; Effauzi, M.; Ritonga, Mahyudin (Letiges, 2024)
This study aims to analyze the public's perception of religious moderation in Indonesia amid diversity and to measure the role of education in instilling the values of religious moderation in Indonesia. To answer these objectives, this research uses qualitative methods, while data collection techniques are carried out through interviews, documentation studies, and the distribution of questionnaires through Google Forms. Data were analyzed through data reduction, data presentation, and conclusion, and data validity checking was done by triangulation. The findings of this study indicate that all elements of the profession are aligned with the internalization of the values of religious moderation in education, both in terms of curriculum subject matter and strengthening teachers' understanding of the concept of religious moderation in Indonesia. The limitation of this study is that researchers have yet to conduct empirical research related to moderation education on the object of research. This research implies that moderation education in educational institutions in Indonesia needs to be expanded, considering the Indonesian state, which consists of various ethnicities, tribes, and cultures. This research is original in terms of the data found, and the analysis carried out, which shows that moderation education according to public perception is very important to be developed, especially in Indonesia.